Comparison of four independently determined structures of human recombinant interleukin-4. - Smith, L; Redfield, C; Smith, R; Dobson, C; Clore, G; Gronenborn, A; Walter, MR; Naganbushan, T; Wlodawer, A (1994)
Four independent structures of human interleukin-4, two determined by nuclear magnetic resonance techniques and two by X-ray diffraction, have been compared in detail. The core of this four helix bundle protein is very similar in all the structures but there are some differences in loop regions that are known to be mobile in solution. Careful comparison of the experimental data sets and the methods of analysis of the different laboratories has provided clues to the sources of most of the differences, and also answered some general questions about the accuracy of protein structure determination by these two techniques.